On the histone lysine methyltransferase activity of fungal metabolite chaetocin. - Cherblanc, F; Chapman, K; Reid, J; Borg, A; Sundriyal, S; Alcazar-Fuoli, L; Bignell, E; Demetriades, M; Schofield, C; DiMaggio, P; Brown, R; Fuchter, M (2013)
Histone lysine methyltransferases (HKMTs) are an important class of targets for epigenetic therapy. 1 (chaetocin), an epidithiodiketopiperazine (ETP) natural product, has been reported to be a specific inhibitor of the SU(VAR)3-9 class of HKMTs. We have studied the inhibition of the HKMT G9a by 1 and functionally related analogues. Our results reveal that only the structurally unique ETP core is required for inhibition, and such inhibition is time-dependent and irreversible (in the absence of DTT), ultimately resulting in protein denaturation. Mass spectrometric data provide a molecular basis for this effect, demonstrating covalent adduct formation between 1 and the protein. This provides a potential rationale for the selectivity observed in the inhibition of a variety of HKMTs by 1 in vitro and has implications for the activity of ETPs against these important epigenetic targets.